The liability of quasi-professionals in the building and construction industry: special reference to negligent certification by public authorities - Abd Rahman, Hussin Mohamed; Abd Ghadas, Zuhairah Ariff; Mohamad, Akmal; Hussin, Mohamad Fahmi; Ali, Zuraidah (2015)
The common law evidently recognized a category of quasi-professionals in the building and construction industry. Within this category are main contractors, specialist sub-contractors, local authority building inspectors and skilled sectors. The retreat after Peabody Donation Fund v. Parkinson & Co. Ltd. and more particularly the change in Murphy v. Brentwood District Council and Caparo Industries Plc. v. Dickman have generated significant shift in relation to the concept of quasi-professional liability and the doctrine of special relationship. This paper discusses the legal principles of professionals’ liability in the building and construction industry and the shift of such liability from the professionals to the quasi professionals. Special reference is made to negligent certification affecting public authorities as an example of quasi -professionals in the construction industry. This paper applies the doctrinal analysis research methodology.